The Universe of Afterlife Intertext in Fantasy of 20th–21th Centuries: The Functionality of Art Model - Elena N. Kovtun (Studia Litterarum)
The article comprises the summarized results of the author’s investigation of the Universe of Afterlife — the post-mortem home of human soul — as a specific locus in Russian, Slavic, European and North American fantasy of 20th–21th centuries. More than a hundred fiction texts under analysis, referring to the genre of fantasy, depict the Universe of Afterlife as an isolated area, unmistakably identified both by the author and the reader, and characterized by its own space-time and landscape parameters, population diversity, system of social and moral norms. The article outlines the invariant features of the Universe of Afterlife narrative, allowing to raise an issue of the unified “Universe of Afterlife Intertext,” inherent in the literature of fantasy of the examined period. Besides, it introduces the images of the meeting guard, mentor or guide, accompanying the personage through the afterlife kingdom. The article proposes the classification of basic models of the Universe of Afterlife according to the criteria elaborated by the author; it also features the most widely-spread plotcomposition schemes of the Universe of Afterlife narrative. The conclusion contains the comprehensive characteristics of the functionality of the Universe of Afterlife art image and the summary of the different writer’s ideas and hypotheses on the aims, meaning and duration (finiteness or eternity) of post-mortem existence.